Sites of invasion of cancer of the external auditory canal predicting oncologic outcomes. Issue 10 (9th July 2021) - Shiga, Kiyoto; Nibu, Ken‐ichi; Fujimoto, Yasushi; Asakage, Takahiro; Homma, Akihiro; Mitani, Hiroki; Ogawa, Takenori; Okami, Kenji; Murono, Shigeyuki; Hirano, Shigeru; Ueda, Tsutomu; Hanai, Nobuhiro; et al.
Abstract: Background: This study aimed to reveal the influence of the invasion site of external auditory canal (EAC) cancer by analyzing the outcome of patients with advanced tumor. Methods: A total of 111 patients with T4 EAC cancer were enrolled in this study. Of these patients, 79 underwent chemoradiotherapy and 32 underwent surgery under curative intent. Univariate and multivariate analyses and the Kaplan–Meier method were used to focus on the tumor invasion sites and overall survival of the patients. Results: The 3‐year overall survival rate of all patients was 55.0%. In multivariate analysis, the only significant invasion site for overall survival was the facial nerve, with the dura mater being the next most influential site. When Kaplan–Meier survival curve was calculated, facial nerve and dura mater were the significant factors resulting in poor patient outcomes. Conclusion: The facial nerve and dura mater are crucial sites of EAC cancer for patient outcomes.